Efficacy and tolerability of very low-volume bowel preparation in patients with inflammatory bowel diseases. Issue 7 (July 2021) - Neri, Benedetto; Scarozza, Patrizio; Giannarelli, Diana; Sena, Giorgia; Mossa, Michelangela; Lolli, Elisabetta; Calabrese, Emma; Biancone, Livia; Grasso, Enrico; Di Iorio, Laura; Troncone, Edoardo; Monteleone, Giovanni; et al.
Abstract : Objectives: An adequate bowel preparation is essential for a quality colonoscopy. Patients with inflammatory bowel disease (IBD) show low compliance with bowel preparation due to the large volume of lavage solution to be ingested, especially if active symptoms are present, and the frequency of having a colonoscopy. We evaluated the efficacy and tolerability of a very low-volume (VLV) polyethylene glycol (PEG)-based solution in patients with IBD. Methods: A cohort of 103 consecutive patients, 56 with Crohn's disease and 47 with ulcerative colitis, received a 1-L PEG-based bowel preparation divided into two 500-mL doses taken the evening before and the morning of the colonoscopy, each dose followed by at least another 500-mL of clear fluids. Colon cleansing was scored according to the Boston Bowel Preparation Scale (BBPS) and evaluated in relation to influencing variables. Results: Bowel cleansing was adequate (BBPS ≥ 6) in 88 patients (85.4%). The time interval between the end of bowel preparation and the beginning of colonoscopy and the disease activity significantly affected colon cleansing. Most patients declared a complete intake of lavage solution (99%), the willingness to repeat the same bowel preparation in a future colonoscopy (86.4%), and a good taste assessment. Conclusion: The VLV PEG-based bowel preparation is effective and well accepted by IBD patients. As minimizing the volume of lavage solution required, the VLV-bowel preparation here tested could be of choice in subjects who perform periodically colonoscopy or in those who do not tolerate a larger amount of liquids.